PERANTI KONJUNGSI DALAM “18 KISAH ORANG BANJAR” KARYA SUPIANI - Eka Suryatin (Balai Bahasa Kalimatan Selatan, 2018)
This paper discusses the use of Indonesian language and Banjar language conjunctions in “18 Banjarese Stories”. The purpose of this study is to describe the use of Indonesian language and Banjar language conjunction devices in “18 Banjar Stories”. This research is a qualitative descriptive study. This research uses an observation method. The data collection techniques are note taking and analyzed with distributional method. The data are sentences or discourse quotation containing conjunction device in “18 Banjar Stories”. The data source of this study is taken from the book of “18 Stories of Banjar people by Supiani, S.Pd. published by Hemat Amuntai, consist of 77 pages in 2016. The results show that the use of conjunction device found in Banjar language are as follows: comparison conjunction devices “as if” (tunang kaya), and “like” (kaya), temporal conjunction devices, “after” (imbah), “then” (lalu), after that (imbahnitu), additive conjunction devices “other than” (salain nangitu), “and” (lawan), adversative conjunction devices (contrast) “but” (tapi), conditional conjunction device “because” (sabab) and exemplifying conjunction device “if” (mun). Meanwhile, the use of Indonesian conjunction devices found in the book “18 Banjar Stories” are additive conjunction device “and” (dan), corrective conjunction device “or” (atau), and temporal conjunction devices “after” (setelah), “then” (lalu), and “next time” (kemudian).Key word: conjunction, discourse, Banjar Language